Papel do receptor B2 de cininas na patogênese e progressão da doença de Alzheimer experimental: da resposta imune à cognição - Viero, Fernanda Tibolla (2019)
Alzheimer's disease (AD) is a complex and progressive neurodegenerative disorder characterized by the decline and loss of cognitive functions, and it is the most common of dementias. The major pathological features of AD are the presence of amyloid plaques which consist of aggregates of amyloid beta peptide (Aβ) and neurofibrillary tangles formed mainly by hyperphosphorylated tau proteins. Among several factors that are involved in the pathogenesis and progression of AD, neuroinflammation is an inherent process in the pathogenesis of AD. Studies show that the kinin system is stimulated by the pathological Aβ in AD patients. The effects of this system are mainly mediated by bradykinin (BK) and its kinin- B2 receptor (B2R) and include the direct action of blood-brain barrier (BBB) permeabilization and inflammation. Thus, we investigated the possible effects of B2R blockade on different AD models: double transgenic male mice (n = 6 to 8) as a family AD model (APPswe / PS1dE9) and oligomeric Aβ peptide injections in C57BL6 males (n = 10), expressing B2R or not and pretreated with saline or B2R antagonist: HOE-140. Acetylcholinesterase levels and BBB permeability were verified after injection with β-amyloid oligomer (AβOS). In addition, object recognition testing was performed on animals aged 3, 6 and 9 months for APPswe / PS1dE9 genotype and 48 hours and 7 days on animals injected with AβOS. The data obtained show the first evidence that AβOS increased BHE permeability and HOE-140 provided significant protection against AβOS effect. Similarly, the B2R antagonist reduced acetylcholinesterase (AchE) activity, suggesting that B2R modulation may act as a new therapeutic strategy for AD, already used clinically to treat hereditary angioedema. Interestingly, both HOE-140 and B2R knockout (B2R-/-) prevented long-term memory decline in AD models. Collectively, these results suggest that B2R blockade may be a target of prophylactic treatment in neurodegeneration deceleration.